2020
DOI: 10.1016/j.dnarep.2020.102967
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrimeric PCNA increases the activity and fidelity of Dbh, a Y-family translesion DNA polymerase prone to creating single-base deletion mutations

Abstract: Dbh is a Y-family translesion DNA polymerase from Sulfolobus acidocaldarius, an archaeal species that grows in harsh environmental conditions. Biochemically, Dbh displays a distinctive mutational profile, creating single-base deletion mutations at extraordinarily high frequencies (up to 50%) in specific repeat sequences. In cells, however, Dbh does not appear to contribute significantly to spontaneous frameshifts in these same sequence contexts. This suggests that either the error-prone DNA synthesis activity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Given the low fidelity of apPol’s nucleotide incorporation opposite this lesion, such bypass might be a major source of mutations within the apicoplast genome. For viral and cellular replisomes from all domains of life, it has been reported that partner proteins such as the processivity factor can increase the fidelity and/or lesion bypass activity of a DNA polymerase, and it remains to be seen if this holds true for apPol-mediated TLS.…”
Section: Discussionmentioning
confidence: 99%
“…Given the low fidelity of apPol’s nucleotide incorporation opposite this lesion, such bypass might be a major source of mutations within the apicoplast genome. For viral and cellular replisomes from all domains of life, it has been reported that partner proteins such as the processivity factor can increase the fidelity and/or lesion bypass activity of a DNA polymerase, and it remains to be seen if this holds true for apPol-mediated TLS.…”
Section: Discussionmentioning
confidence: 99%